2011
DOI: 10.4028/www.scientific.net/amm.108.194
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Kappa-Carrageenan Oligosaccharides

Abstract: Κ-carrageenan oligosaccharides were prepared by enzymatic degradation. The inhibiting activities of the prepared κ-carrageenan oligosaccharides against Escherichia coli (E.coli ), Staphylococcus aureus (S.aureus), Saccharomyces cerevisiae (S.cere), Penicillium citrinum (P.citr) and Mucor.sp were determined and compared by measuring the inhibitory zone diameter. The results indicate that all tested κ-carrageenan oligosaccharides have inhibiting activity against the five bacteria, but the inhibiting activities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 6 publications
1
17
0
1
Order By: Relevance
“…Kappa carrageenan and lambda carrageenan showed an increase of growth in E. cloaceae by 18.0% and 17.44% respectively (Figure 7). Although the results of bacterial growth inhibition obtained from carrageenan were not that quite high for S. aureus, it indeed showed that it has antibacterial activity as previously reported [20]. Figure 8, Figure 9 showed the paper strip test for combined action of double layer and multilayers of carrageenan and PEI.…”
Section: Bacterial Growth Inhibitionmentioning
confidence: 50%
See 1 more Smart Citation
“…Kappa carrageenan and lambda carrageenan showed an increase of growth in E. cloaceae by 18.0% and 17.44% respectively (Figure 7). Although the results of bacterial growth inhibition obtained from carrageenan were not that quite high for S. aureus, it indeed showed that it has antibacterial activity as previously reported [20]. Figure 8, Figure 9 showed the paper strip test for combined action of double layer and multilayers of carrageenan and PEI.…”
Section: Bacterial Growth Inhibitionmentioning
confidence: 50%
“…In one study, oligosaccharides from κ-carrageenan have antibacterial activities against E. coli, S. aureus, S. cere, P. citr and Mucor sp. [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, depending on their molecular weight, several of the CG molecular chains were comprised of two or more monosaccharides that could link to glycoproteins and are associated with the outer side of the bacterial cytoplasmic membrane, especially in Gram‐negative bacteria . It has been reported by Wang et al that short chains of CG have antimicrobial activity. According to their research findings, however, the mechanism by which cell death occurs is not well known.…”
Section: Discussionmentioning
confidence: 99%
“…According to their research findings, however, the mechanism by which cell death occurs is not well known. Potentially, the union of these chains to the surface of the bacteria produces structural changes in the membrane, increasing the permeability and leading to bacterial death …”
Section: Discussionmentioning
confidence: 99%
“…Another way to evaluate the antibacterial efficacy of carrageenans was through the use of kappa -CG oligosaccharides against Escherichia coli , Staphylococcus aureus , Saccharomyces cerevisiae , Penicillium citrinum , and Mucor spp., determining the antibacterial efficacy by measuring the diameter of the inhibitory zone. Consequently, it was observed that all kappa -CG oligosaccharides had inhibitory activity against the bacteria studied, presenting a greater inhibitory activity against Saccharomyces cerevisiae [ 78 ].…”
Section: Bioactive Properties Of Carrageenanmentioning
confidence: 99%